2015
DOI: 10.1002/ange.201503247
|View full text |Cite
|
Sign up to set email alerts
|

Übergangsmetallkatalysierte Wasserstofftransferanellierungen: Zugang zu heterocyclischen Gerüsten

Abstract: Übergangsmetall‐Wasserstofftransferkatalysatoren ermöglichen ausgehend von einfachen Ausgangsmaterialien einen schnellen Zugang zu wichtigen Strukturmotiven, so auch zu Heterocyclen. Übergangsmetallkatalysierte Wasserstofftransferanellierungen sind umweltverträglich und in hohem Maße atomökonomisch, da sie Wasser und Wasserstoff als Nebenprodukt freisetzen und erneuerbare Alkohole als Ausgangsmaterialien verwenden. Hier werden neueste Fortschritte auf diesem Gebiet im Hinblick auf Anellierungen von Alkoholen m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…To circumvent this drawback, alkaline metal compounds (hydroxides and alkoxides) have been investigated and successfully replaced aluminum alcoholates to convert alcohols into aldehydes or ketones through hydrogen autotransfer process [6,7] . Recently, several research groups have reported effective strategies for the extension of carbon chain, [8] N ‐alkylation of amines, [9] amidation, [10] and the preparation of heterocycles via base‐mediated intermolecular hydrogen transfer [11] . For example, Zhu and co‐workers investigated the synthesis of functionalized quinolines by an intramolecular hydrogen transfer process of 2‐nitrobenzyl alcohol with ketones in the presence of t ‐BuOK (Scheme 1a) [12] .…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this drawback, alkaline metal compounds (hydroxides and alkoxides) have been investigated and successfully replaced aluminum alcoholates to convert alcohols into aldehydes or ketones through hydrogen autotransfer process [6,7] . Recently, several research groups have reported effective strategies for the extension of carbon chain, [8] N ‐alkylation of amines, [9] amidation, [10] and the preparation of heterocycles via base‐mediated intermolecular hydrogen transfer [11] . For example, Zhu and co‐workers investigated the synthesis of functionalized quinolines by an intramolecular hydrogen transfer process of 2‐nitrobenzyl alcohol with ketones in the presence of t ‐BuOK (Scheme 1a) [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transition-metal-catalyzed tandem reactions have become an efficient strategy for the construction of structurally complex molecules in organic synthesis, 8 which has been successfully applied in the preparation of substituted quinolines. 9 For example, Shi, 9a Xia, 9b Xu, 9c Li, 9d and Chen 9g have reported impressive procedures to substituted quinolines starting from azide-methylenecyclopropanes, 1,7-enynes, alkyne-tethered diazo compounds, o-cyanoarylacrylamides, and N-aryl azoles, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%